Contribución al conocimiento de la flora pteridológica de El Hierro (Islas Canarias) - Peroni, A.; Peroni, G.; Bonalberti, C. (Botanica Complutensis, 2001)
BONALBERTI PERONI, C., PERONI, A. & PERONI, G. 2001. Contribution to the knowledge of the Pteridoligical Flora of El Hierro (Canary Islands). Bot. Complutensis 25: 289-297. A study on the Pteridophyta of El Hierro, the western island of the Canary Archipelago, was realized. A census of 30 taxa subdivided in 12 families was made. Some notes have a greatest importance for the rareness of species or for ecological conditions where taxa vegetate.